Small Nuclear Ribonucleoprotein Polypeptide N Accelerates Malignant Progression and Poor Prognosis in Colorectal Cancer Transcriptionally Regulated by E2F8 - Ji, Meiling; Ren, Li; Lv, Yang; Lao, Xinyuan; Feng, Qingyang; Tang, Wentao; Zhuang, Aobo; Liu, Tianyu; Zheng, Peng; Xu, Jianmin (Frontiers in Oncology, 2020)
Colorectal cancer is a major cause of death worldwide, and the identification of new diagnostic and prognostic biomarkers are crucial to develop new strategies to avoid colorectal cancer-related deaths. Small nuclear ribonucleoprotein polypeptide N (SNRPN) is an imprinted gene that plays an important role in various neurodevelopmental disabilities. In this study, SNRPN was highly expressed in colorectal cancer tissues, and involved in the progression of this disease. Immunohistochemistry analysis of 1310 colorectal cancer tissue samples showed that SNRPN highly expressed in cancer tissues than in adjacent tissues, and was mainly localized in the nucleus. Clinical pathological factor analysis demonstrated that higher expression of SNRPN was significantly associated with larger tumor size, location of the colon on the left-side, neural invasion, and distant metastasis. Univariate and multivariate analyses showed that SNRPN expression was an independent risk factor for survival, with high expression levels indicating worse overall survival. Both in vitro and in vivo experiments confirmed that high expression of SNRPN was associated with tumor proliferation, cell cycle, and metastasis. Knocking down SNRPN blocked the cell cycle at the G2/M phase transition and promoted tumor cell apoptosis, inhibiting the progression of colorectal cancer. To explore the up-steam of SNRPN, we found E2F8 positively transcriptional regulate it in CRC by luciferase reporter assay and chromosomal immunoprecipitation assay. Systematic studies of SNRPN will help us discover new regulatory molecules and provide a theoretical basis for finding new molecular targets for this disease.